Improved threshold fouling models for crude oils - Shetty, N. (Elsevier Ltd, 2016)
The existing threshold fouling models always predict an increase in initial fouling rates with an increase in bulk temperature which may not hold good for some crude oils. In this study, an improved threshold fouling model is proposed which uses an effective film temperature in the Arrhenius expression. Experiments were conducted in a high pressure, high temperature recirculation flow pilot-scale fouling test rig with three test crude oils with differing properties under the operating conditions of surface and bulk temperatures ranging from 243 to 334 °C and 82-180 °C, respectively, and velocities at 0.35 and 0.5 m/s. The proposed model has been shown to predict initial fouling rates very closely with the experimental data with R2 values above 0.98 for the three test crude oils used in this study. © 2016 Elsevier Ltd.